2020
DOI: 10.3390/ijerph17124490
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Muscle Energy Technique versus Osteopathic Manipulation in the Treatment of Sacroiliac Joint Dysfunction in Athletes

Abstract: Background: The study of injuries stemming from sacroiliac dysfunction in athletes has been discussed in many papers. However, the treatment of this issue through thrust and muscle-energy techniques has hardly been researched. The objective of our research is to compare the effectiveness of thrust technique to that of energy muscle techniques in the resolution of sacroiliac joint blockage or dysfunction in middle-distance running athletes. Methods: A quasi-experimental design with three measures in time (pre-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The results of this study are somewhat similar to those presented in a study performed among athletes with SiJd, comparing MET and osteopathic manipulation [28]. it was concluded that MET and manipulation both demonstrated significant results in athletes with SiJd but the improvement in the MET group was seen after the initial intervention only.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study are somewhat similar to those presented in a study performed among athletes with SiJd, comparing MET and osteopathic manipulation [28]. it was concluded that MET and manipulation both demonstrated significant results in athletes with SiJd but the improvement in the MET group was seen after the initial intervention only.…”
Section: Discussionsupporting
confidence: 87%
“…Vaseghnia et al in 2019 claimed that Post isometric relaxation in short term significantly reduced the VAS and MODI in females with anterior innominate dysfunction also supported my study. On recommendation of this study, long term effects of Post isometric relaxation for treatment of anterior innominate dysfunction for better outcomes were checked in current study both in males and females gender (13) The current study contrasts together with a study conducted by Urko Jose et al (2019) on muscle energy technique contrasted with osteopathic manipulations in management of SIJD in players concluded that Thrust approach produced significantly improvement in pain and disability in long term and muscle energy technique was effective for short term (25). But current study claimed that post isometric relaxation was also effective for pain and disability in long term as compared to static stretching.…”
Section: Resultsmentioning
confidence: 78%
“…Manipulation is a common therapy for SIJ dysfunction [7][8][9][10] . At present, there are many clinical reports on the treatment of SIJ dysfunction by manipulation of oblique-pulling (MOP) [11][12][13] , but there are few studies about the mechanism of manipulation.…”
Section: Introductionmentioning
confidence: 99%